Microfluidic Single-Cell Analysis of Transplanted Human Induced Pluripotent Stem Cell–Derived Cardiomyocytes After Acute Myocardial Infarction. Issue 8 (25th August 2015) - Ong, Sang-Ging; Huber, Bruno C.; Hee Lee, Won; Kodo, Kazuki; Ebert, Antje D.; Ma, Yu; Nguyen, Patricia K.; Diecke, Sebastian; Chen, Wen-Yi; Wu, Joseph C.
<x xml:space="preserve">Abstract</x> Background— Human induced pluripotent stem cells (iPSCs) are attractive candidates for therapeutic use, with the potential to replace deficient cells and to improve functional recovery in injury or disease settings. Here, we test the hypothesis that human iPSC-derived cardiomyocytes (iPSC-CMs) can secrete cytokines as a molecular basis to attenuate adverse cardiac remodeling after myocardial infarction. Methods and Results— Human iPSCs were generated from skin fibroblasts and differentiated in vitro with a small molecule–based protocol. Troponin+ iPSC-CMs were confirmed by immunohistochemistry, quantitative polymerase chain reaction, fluorescence-activated cell sorting, and electrophysiological measurements. Afterward, 2×106 iPSC-CMs derived from a cell line transduced with a vector expressing firefly luciferase and green fluorescent protein were transplanted into adult NOD/SCID mice with acute left anterior descending artery ligation. Control animals received PBS injection. Bioluminescence imaging showed limited engraftment on transplantation into ischemic myocardium. However, magnetic resonance imaging of animals transplanted with iPSC-CMs showed significant functional improvement and attenuated cardiac remodeling compared with PBS-treated control animals. To understand the underlying molecular mechanism, microfluidic single-cell profiling of harvested iPSC-CMs, laser capture microdissection of host myocardium, and in vitro ischemia stimulation were used to demonstrate that the iPSC-CMs could release significant levels of proangiogenic and antiapoptotic factors in the ischemic microenvironment. Conclusions— Transplantation of human iPSC-CMs into an acute mouse myocardial infarction model can improve left ventricular function and attenuate cardiac remodeling. Because of limited engraftment, most of the effects are possibly explained by paracrine activity of these cells.